Condylomata acuminata – treatment - Kowzan-Korman, Alicja (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Condylomata acuminata are benign verrucose forms localised usually in the anogenital region and caused by human papilloma virus infection (mostly by HPV-6 and HPV-11). Anogenital inflammation changes, tissue lesions and immunodeficiency are conducive to the development of condylomata acuminata. The usual ways of HPV transmission include sexual intercourses, labour and hygienic neglect. This article reviews up-to-date knowledge on contemporary treatment methods of condylomata acuminata.